Opera omnia Desiderii Erasmi Roterodami: recognita et adnotatione critica instructa notisque illustrata / Ordo 1, Tomus 1 - Erasmus, Desiderius (Opera omnia Desiderii Erasmi Roterodami recognita et adnotatione critica instructa notisque illustrata, 1969)
Inhalt: General introduction -- Antibarbarorum liber, ed. Kazimierz Kumaniecki - Commentarius Erasmi in nucem Ouidii, ed. R.A.B. Mynors - Libanii aliquot declamatiunculae Latinae per Erasmum, R.A.B Mynors - Euripidis Hecuba et Iphigenia Latinae factae Erasmo interprete, ed. Jan Hendrik Waszink - Luciani compluria opuscula ab Erasmo et Thoma Moro interpretibus optimis in Latinorum linguam traducta, ed. Christopher Robinson - Galeni exhortatio ad bonas arteis praesertim medicinam, de optimo docendi genere, et qualem oporteat esse medicum, Erasmo interprete, ed. Jan Hendrik Waszink - List of abbreviations,Index nominum -- The first volume of the first Ordo of the Amsterdam edition of the Latin texts of Erasmus contains a general introduction, and presents Erasmus’ attack on barbarous Latin, a commentary on Ovidius’ poem Nux, as well as Erasmus’ Latin translations of Euripides’ Hecuba and Iphigenia, declamations of Libanius, and works by Lucianus and Galenus. The volume offers a critical edition of the Latin text with introductions, and a commentary in English offering background information that helps to understand the text, and an evaluation of Erasmus’ translations. (Verlagsinformation)